Pioneer vegetation groupings and some approaches to the artificial overgrowth of highway slopes of piedmont Dagestan, Russia - Z. M. Asadulaev; G. A. Sadykova; M. M. Mallaliev; Z. R. Ramazanova; N. V. Mishchenko; S. L. Desinov; S. L. Asadulaev (Юг России: экология, развитие)
Aim. Detection of succession trends and bioengineering approaches to the restoration of vegetation on road slopes of piedmont Dagestan in Russia.Material and Methods. Ten test area plots (100 m2 every 500m) at 256‐515m altitude and at a range of exposures were established along the Makhachkala‐Buinaksk highway (Narat‐Tyube Pass section) to assess species composition and their participation in the overgrowth of roadside slopes.Results. This paper presents the results of studying the primary overgrowth of roadside slopes in the conditions of piedmont Dagestan. Data are presented on the natural vegetation, geomorphology, soil types and parent rocks of the Narat‐Tyube ridge. In the first year of observations, a spectrum of families with the largest number of pioneer species and the role of slope consolidation with a high proportion of vegetatively propagating species was determined.Conclusions. Native woody species showing promise for the application of bioengineering methods for optimization and acceleration of vegetation overgrowth have been identified. Features of overgrowth species distribution in relation to slope microenvironments, proximity of natural plant communities and their ecological and biological characteristics have been shown.